EFFECT OF THINNING INTENSITY ON THE MENSURATION PARAMETERS OF OAK STANDS IN FRESH MAPLE-LIME OAK FOREST IN THE LEFT-BANK FOREST-STEPPE - Lunachevskyy, L. S.; Rumiantsev, M. Н. (Forestry and Forest Melioration, 2017)
Introduction Productivity and quality of oak forests largely depend on site conditions, health condition, composition, age, the stand density and forest management. The current state of oak stands shows the insufficient use of the potential productivity of habitat conditions, the presence of large areas with poor stand composition and unsatisfactory health condition. An important activity to increase the productivity, to preserve biological sustainability and biodiversity of planted oak forests and to provide their protective functions is tending felling. Despite significant scientific contributions on improvement felling in oak stands, the issues concerning intensity and frequency of their performing, as yet, are debatable. Materials and Methods Research methodology included characteristics of oak stands using methods generally accepted in forestry and forest inventory. The study was carried out in the experiment on tending felling intensity effect on the growth of planted oak stands, established by M. L. Pestenko in 1929 in 29-year-old stands in Trostyanetske Forestry Enterprise, in Neskuchanske forestry. Forest planting was created using English oak (Quercus robur L.), European ash (Fraxinus excelsior L.) and Norway maple (Acer platanoides L.). the planting pattern was as follows: mixing three rows of English oak, one row of Norway maple and one row of European ash. Experimental tending felling, records, and measurements were carried out in 1929, 1930, 1935, 1945 and 1963. After 1963, only selective sanitation felling was performed during which only naturally dead trees were removed. Results In experimental plantations, at the age of 114 years, high-density and high-productive stands of mixed composition were formed. The stocking was 0.75 (low intensity of thinning) and 0.89 (heavy thinning). The results of 85 years of research show the effects of thinning on dynamics of mensuration parameters of artificial ash and oak stands in a fresh fertile site condition. It was found that after the thinning, the stock volume and the height of the stands at the section with heavy thinning were lower than those at the section with low thinning intensity, and the diameter of the main species was slightly larger. However, after the age of 60, the mensuration values of the experimental stands became similar. At the experimental section, where heavy thinning was carried out, at the age of 114 years, the oak stands had higher mensuration parameters, productivity, and volume of merchantable wood and the better health and assortment structure, compared to the oak plantations in the section with low thinning intensity. Conclusions Mixed planted oak stands in the conditions of fresh maple-lime oak forest in the Left-bank Forest-Steppe of Ukraine should be grown at the age of 21–40 years applying heavy thinning. During the first thinning, a moderate intensity of thinning should be applied. Starting from 60–65, tending felling should not be carried out, but limited to selective sanitation felling, not allowing accumulation of dead standing trees in the stand. In such plantations, even tending felling of heavy intensity allows forming a mature stand with the density of about 0.9, which grows by the 1st site class. 1 Fig., 4 Tables, 13 Refs.